(3GdfXGe GdGMUGFj (BSPSS :s (3age hJMdjd GdHjGfGJ ddEMUGFjI (B/s - (3GdRZHj, eMeO HdGds; (3GdWdGaMI, YHGS C(B.s ((3YeGf(B: s (3OGQ hGFd ddWHGYI hGdfTQ(B, s, 2003)
(3jMJhj gPG GdcJGH Ydi LhGfH GdJj jMJGLgG GdHGMK HTcd eJSdSd heaUd aaj GdaUd GdChd ebOeI Edi Yde GdGMUGA hJYQja HGdeJZjQGJ hCfhGYgG hGdYjfGJ hWQb LeY GdHjGfGJ GMJhi GdaUdGf GdKGfj hGdKGdK GdNWhGJ GdJGdjI HYO LeY GdHjGfGJ hgj YedjI GdJQejR hGONGd GdHjGfGJ GdJYGed eY GdedaGJhJLgjRGgG JegjO dYedjI GdJMdjd hGTJed GdaUd GdQGHY Ydi GdGLQGAGJ GdJfXjejI ddedaGJ GdJj JSHb YedjI GdJMdjd ef GfTGA deJZjQGJ LOjOI SJSJNOe aj GdJMdjd Ch GYGOI dJQejR GdeJZjQGJ GdehLhOI hPdc JegjO GdJMdjd , CeG GdaUhd GdJGdjI abO JfGhdJ YedjGJ JMdjd GdHjGfGJ aaj GdaUdjf GdNGeS hGdSGOS TQM ddGLQGAGJ GdGMUGFjI GdJj JSJNOe dhUa GdeJZjQGJ HLejY CfhGYgG ShGA ef NdG GdWQb GdhUajI GdQbejI Ce GdQShe GdHjGfjI hbO CVja GLQGA (Bcrosstals (3GNJHGQ eQHY cGj hJWQbJ GdaUhd (B7-8-9- (3Edi GdWQb GdGMUGFjI GdeJbOeI GdeSJNOeI dGLQGA GdGNJHGQGJ GdGMUGFjI JegjO dGJNGP GdbQGQGJ , hPdc ef NdGd eLehYI ef GdGeKdI GdMbjbjI deTcdGJ HMKjI (B.s
Keywords: (3GdHQeLIs; (3fXGe GMUGFjs; spss (3GdMGShHs